Current trends in emergency airway management: a clinical review - Sangun Nah; Yonghee Lee; Sol Ji Choi; Jeongwoo Lee; Soyun Hwang; Seongmi Lim; Inhye Lee; Young Soon Cho; Hyun Soo Chung (Clinical and Experimental Emergency Medicine)
Airway management is a fundamental and complex process that involves a sequence of integrated tasks. Situations requiring emergency airway management may occur in the emergency department, intensive care units, and various other clinical settings A variety of challenges can arise during emergency airway preparation, intubation, and postintubation, which may result in significant complications for patients. Therefore, many countries are establishing step-by-step systemization and detailed guidelines and/or updating their content based on the latest research. This clinical review discusses the current trends in emergency airway management, such as emergency airway management algorithms, comparison of video and direct laryngoscopy, rapid sequence intubation, pediatric airway management, prehospital airway management, surgical airway management, and airway management education.